The impact of early season insecticides on biological control of apple leafcurling midge (Dasineura mali) - Shaw, P.W.; Wallis, D.R.; Rogers, D.J. (New Zealand Plant Protection, 2003)
The fate of apple leafcurling midge (ALCM Dasineura mali) egg batches was monitored in spring 2003 at two apple orchards in Riwaka near Motueka Orchard A had received prebloom insecticide applications of chlorpyrifos and carbaryl for fruit thinning each season since 2000 Orchard B substituted these chemicals with the selective insecticide buprofezin and used benzyladenine for fruit thinning over the same period Predation and parasitism of ALCM eggs at orchard B resulted in lower survival of larvae and less damage to shoots compared to orchard A Ninety percent of ALCM larvae at orchard B were parasitised by Platygaster demades compared with only 3 at orchard A Heavy infestation of shoots by second generation midge larvae at orchard A resulted in premature termination of 69 of growing shoot tips These results suggest that nonselective early season insecticides used in pipfruit spray programmes may disrupt biological control of ALCM